The impact of policy measures on future power generation portfolio and infrastructure: A combined electricity and CCTS investment and dispatch model (ELCO) - Roman Mendelevitch; Pao-Yu Oei (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
This paper presents a general electricity-CO2 (ELCO) modeling framework that is able to simulate interactions of the energy-only market with different forms for national policy measures. We set up a two sector model where players can invest into various types of generation technologies including renewables, nuclear and Carbon Capture, Transport, and Storage (CCTS). For a detailed representation of CCTS we also include industry players (iron and steel as well as cement), and CO2 transport and CO2 storage including the option for CO2 enhanced oil recovery (CO2-EOR). The players maximize their expected profits based on variable, fixed and investment costs as well as the price of electricity, CO2 abatement cost and other incentives, subject to technical and environmental constraints. Demand is inelastic and represented via a selection of type hours. The model framework allows for regional disaggregation and features simplified electricity and CO2 pipeline networks. The model is balanced via a market clearing for the electricity as well as CO2 market. The equilibrium solution is subject to constraints on CO2 emissions and renewable generation share. We apply the model to a case study of the UK Electricity Market Reform to illustrate the mechanisms and potential results attained from the model.
Keywords: C61; L94; O33; Q42; 330; energy policy; electricity; CO2; CCS; UK; EOR; modeling